Self-assembling dipeptide antibacterial nanostructures with membrane disrupting activity. Issue 1 (December 2017) - Schnaider, Lee; Brahmachari, Sayanti; Schmidt, Nathan; Mensa, Bruk; Shaham-Niv, Shira; Bychenko, Darya; Adler-Abramovich, Lihi; Shimon, Linda; Kolusheva, Sofiya; DeGrado, William; Gazit, Ehud
Abstract Peptide-based supramolecular assemblies are a promising class of nanomaterials with important biomedical applications, specifically in drug delivery and tissue regeneration. However, the intrinsic antibacterial capabilities of these assemblies have been largely overlooked. The recent identification of common characteristics shared by antibacterial and self-assembling peptides provides a paradigm shift towards development of antibacterial agents. Here we present the antibacterial activity of self-assembled diphenylalanine, which emerges as the minimal model for antibacterial supramolecular polymers. The diphenylalanine nano-assemblies completely inhibit bacterial growth, trigger upregulation of stress-response regulons, induce substantial disruption to bacterial morphology, and cause membrane permeation and depolarization. We demonstrate the specificity of these membrane interactions and the development of antibacterial materials by integration of the peptide assemblies into tissue scaffolds. This study provides important insights into the significance of the interplay between self-assembly and antimicrobial activity and establishes innovative design principles toward the development of antimicrobial agents and materials. Peptide-based supramolecular assemblies are a promising class of nanomaterials with important biomedical applications, but their antibacterial properties can be overlooked. Here the authors show the antibacterial activity of self-assembled diphenylalanine, which emerges as the minimal model for antibacterial supramolecular polymers.